2000
DOI: 10.1038/35004539
|View full text |Cite
|
Sign up to set email alerts
|

Molecular control over Au/GaAs diodes

Abstract: The use of molecules to control electron transport is an interesting possibility, not least because of the anticipated role of molecules in future electronic devices. But physical implementations using discrete molecules are neither conceptually simple nor technically straightforward (difficulties arise in connecting the molecules to the macroscopic environment). But the use of molecules in electronic devices is not limited to single molecules, molecular wires or bulk material. Here we demonstrate that molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
303
2
3

Year Published

2001
2001
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 334 publications
(319 citation statements)
references
References 27 publications
11
303
2
3
Order By: Relevance
“…[64] Such molecules are expected to conduct much better than alkyl monolayers. MOMS research, though, is mostly limited to simple alkanes.…”
Section: Other Work On Molecular Electronics With Simentioning
confidence: 99%
See 3 more Smart Citations
“…[64] Such molecules are expected to conduct much better than alkyl monolayers. MOMS research, though, is mostly limited to simple alkanes.…”
Section: Other Work On Molecular Electronics With Simentioning
confidence: 99%
“…(1)), the same cannot be said about the critical role of interface dipoles that form upon bonding at any inorganic interface [13,14] and act to minimize C SC by Le Chatelier's principle (negative feedback). [13,14] We [3,64,109,110] and others [63,[111][112][113] have shown that adsorbing molecules with intrinsic dipoles and/or polar bonding to a solid can change the barrier height for transport in an MS/MIS junction. The theoretical potential drop, C I , can be calculated from: [114,115] .…”
Section: Dipolar Effects Of the Molecular Monolayermentioning
confidence: 99%
See 2 more Smart Citations
“…Instead, a more versatile approach can be envisaged through the exploitation of molecular species in self assembled monolayers. 27 Molecules, unlike inorganic wide bandgap semiconductors, possess a plurality of structural parameters that can be tuned in these systems: the length of the molecule, the conjugated or aliphatic character and the end-functional groups that serve to strongly bind on a given surface and passivate electronic defect states. [27][28][29][30][31][32][33][34][35] Not to exclude also their solution processability which is a significantly lower cost manufacturing process compared to atomic layer deposition.…”
Section: Introductionmentioning
confidence: 99%